1989
DOI: 10.1111/j.1476-5381.1989.tb16897.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of isobutylmethylxanthine and milrinone on ischaemia‐induced arrhythmias and platelet aggregation in anaesthetized rabbits

Abstract: IThe aim of this study was to compare the effects of the non-selective phosphodiesterase (PDE) inhibitor, isobutylmethylxanthine (IBMX) and the selective PDE III inhibitor, milrinone, in a rabbit model of acute myocardial ischaemia. 2 Coronary artery occlusion caused changes in the ST-segment of the ECG and ectopic activity in all control rabbits. Ventricular fibrillation occurred in 10 out of 14 (71%) of these animals. Pretreatment with IBMX 1004ugkg-1 plus 1O0gkg-1min-', starting 10min before coronary art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…Both clinical and experimental studies have suggested that PDE III inhibitors such as amrinone and milrinone can have arrhythmogenic effects during myocardial ischaemia or reperfusion (Collucci et al, 1986;Lukas & Ferrier, 1988;Lynch et al, 1989). Although we did not see any significant arrhythmogenic activity with milrinone in our previous study in rabbits (Holbrook & Coker, 1989) it is possible that a higher dose may have exacerbated arrhythmias. The doses of rolipram used in the present study were chosen on the basis of its reported relative potency as an inhibitor of certain PDE isoenzymes and from preliminary experiments on its effects on heart rate, arterial blood pressure and LVdP/dtmax in anaesthetized rabbits in our laboratory.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…Both clinical and experimental studies have suggested that PDE III inhibitors such as amrinone and milrinone can have arrhythmogenic effects during myocardial ischaemia or reperfusion (Collucci et al, 1986;Lukas & Ferrier, 1988;Lynch et al, 1989). Although we did not see any significant arrhythmogenic activity with milrinone in our previous study in rabbits (Holbrook & Coker, 1989) it is possible that a higher dose may have exacerbated arrhythmias. The doses of rolipram used in the present study were chosen on the basis of its reported relative potency as an inhibitor of certain PDE isoenzymes and from preliminary experiments on its effects on heart rate, arterial blood pressure and LVdP/dtmax in anaesthetized rabbits in our laboratory.…”
Section: Discussioncontrasting
confidence: 77%
“…The doses of rolipram used in the present study were chosen on the basis of its reported relative potency as an inhibitor of certain PDE isoenzymes and from preliminary experiments on its effects on heart rate, arterial blood pressure and LVdP/dtmax in anaesthetized rabbits in our laboratory. Although rolipram is slightly less potent as an inhibitor of PDE IV than milrinone is as an inhibitor of PDE III (Beavo, 1988), we decided to use rolipram in the same doses that we had used milrinone previously (Holbrook & Coker, 1989). A major reason for this decision was that we wanted to avoid causing large reductions in arterial pressure with rolipram because we had evidence that the rabbits which received milrinone and subsequently fibrillated during myocardial isch- aemia were those in which milrinone caused greater decreases in blood pressure (see Holbrook & Coker, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, one conclusion that was drawn from studies with certain phosphodiesterase inhibitors was that increasing cardiac cyclic GMP may be antiarrhythmic (Holbrook & Coker, 1989). Although we have performed further studies with phosphodiesterase inhibitors, no firm conclusions about the possible influence of cyclic GMP on arrhythmias could be drawn from these experiments because we could not detect selective increases in cardiac cyclic GMP without concomitant increases in adenosine 3':5'-cyclic monophosphate (cyclic AMP) (Barnes, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Here the sign + indicate, the mice survived at least 5 days optimal dose of the compound in the circulation achieved through oral administration of aspirin is not known. In the initial phase of the study anesthetic agents are not used for their well known antiplatelet and other hematologic effects [35,36], in latter part of the study it was found that to minimize the pain and suffering, the use of morphine sulfate (200 lg/kg body weight) in these animal model did not interfere with the effect of aspirin in thrombolysis.…”
Section: Discussionmentioning
confidence: 99%